Perancangan Sistem Mekanik Penggerak Sumbu X Dan Y Pada Mesin CNC (Computer Numerical Control) CO2 Laser Cutting - Kusmayanto, Ridwan; Heryana, Ghany; Jatira (Politeknik Negeri Indramayu, 2023)
CO2 Laser Cutting CNC Machine is a machine that uses a laser beam to cut or engrave certain materials. This machine is intended for small and medium enterprises (SMEs), one of which can help craftsmen to produce creative products such as accessories, handicrafts, decorations and others. The CO2 Laser Cutting CNC machine consists of several components, namely the machine frame, stepper motor, timing pulley, timing belt, shaft and bearings. With the above components are expected to work properly. The results of the design of the CO2 Laser Cutting CNC machine have dimensions of 1500 mm in length, 1200 mm in width and 330 mm in height. for the driving source using stepper motors on the X and Y axes with a torque issued by the X axis of 0.113 Nm and the greatest power on the X axis of 3.54 Watt, while the torque released on the Y axis is 0.2073 Nm and the greatest power on the Y axis is 6.5 Watt. The selected motor is a Nema 17HS4401 stepper motor and the transmission system uses a timing pulley and timing belt.